Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany